Optimizing the Role of Production Assistants: The Key to Production Efficiency in the 'Food Diary' Program on iNews - Rahayu, Khairunnisa; Suparman (IJESS International Journal of Education and Social Science, 2025)
This study discusses the optimization of the role of Production Assistants (PAs) in improving the production efficiency of the "Food Diary" program on iNews. Although the PA position is often considered an entry-level position, this role is actually very crucial. Although PAs are not fully responsible for the entire program production, PAs hold significant responsibility in maintaining the smooth running of the television production process. The issues examined in this study include the role of PAs from the pre-production to post-production stages, as well as the extent of PAs' contribution to improving the production efficiency of the "Food Diary" program on iNews. The purpose of this study is to determine the real contribution of PAs to production efficiency and understand strategies for optimizing their role in television program production activities. This study uses a qualitative method with a descriptive approach. Data collection was carried out through in-depth interviews, direct observation, and documentation. The results show that PAs are actively involved in all stages of production, from ensuring the readiness of equipment and logistics during pre-production, maintaining technical smoothness and crew coordination during production, to assisting in the editing process, searching for graphic materials, adding background sound, and finalizing the final broadcast during the post-production stage. Optimizing the role of a PA can be achieved by improving communication skills, time management, and technical knowledge in production. PAs significantly contribute to increasing production efficiency, both in terms of time, inter-team coordination, and technical smoothness in the field.